Relasi Kekuasaan Komisi Yudisial - Dewan Perwakilan Rakyat dan Presiden dalam Pengangkatan Hakim Agung (Dialogia Iuridica, 2016)
This research aim to answer 2 (two) problems in accordance to relation of authority of Judicial Commision-House of Representative and President in promoting supreme judges. First, this article analyze model of relation of authority between Judicial Commision-House of Representative and President in promoting supreme judges in Indonesia. Second, the article analyze implication of Constitutional Courtâ€™s Verdict Number 27/PUU-XI/2013 to relation of authority between Judicial Commision-House of Representative and President in promoting supreme judges in Indonesia.This article is using qualitative descriptive method. Type of research is normative juridical by exercising library research on study of positive law and nature of prescriptive.This article conclude that (1), basically, relation of authoritybetween Judicial Commision-House of Representative and President designed to create check and balance principle in promoting supreme judges. Existency and involvement of Judicial Commision in democratic transition was expected as an answer and ending of bitter history in previous mechanism in promoting supreme judges which loaded with intervention of rulers. That expectation was not propotional when integrated to level of statute. Friction of paradigm occurred when House Representative expropriate the role as main actor in promoting supreme judge and negate the roles of Judicial Commision to relation of Authority which based on ratio. This friction triggered by accidental amandement of constitution, which evoke strong wave of reformation and the effort in preserving back classic model. (2), after the verdict of Constitutional Court issued, there are logic consequence to relation of Authority between Judicial Commision-House of Representative and Presidentin promoting supreme judges. Legally, it caused to inconstitutionality of ratio-based relation of authority. It also cause adisapovowal of fit and proper test of House of Representative, productivity of Supreme Court and inefficiency of budget. An idea to improve should be taken by creating corporate culture, changing flow of supervision of House of Representative and emerging mutual trust between involved organs in relation to promote supreme judges. That idea intended to transform inconstitutionality of â€œrasio-basedâ€ relation of authority into â€œtrust-basedâ€ relation of authority.